Values of Economists Matter in the Art and Science of Economics. (15th March 2019) - van Dalen, Hendrik P.
Summary: What role do personal values play in the practice of economists? By means of a survey among economists working inside and outside academia in the Netherlands, we present novel insights on their personal values, how these differ from the average citizen, and how values impact their economic views and their methodological choices. Three overarching values summarize the value structure of economists: achievement, serving the public interest, and conformity to rules. Subsequent tests are performed to see whether these values affect (1) their opinion on economic propositions and (2) their attitudes towards methodological principles in economics. For the majority of economic propositions, personal values matter. Especially the value of serving the public interest has a strong effect on their economic view. Furthermore, it seems that economists who value achievement are the ones who are more likely to embrace mainstream methodological principles: thinking predominantly in terms of efficiency, rationality, and competition, believing that economic knowledge is objective and transparently produced and in agreement with Milton Friedman's view on positive economics. Female economists are at some notable points less convinced of market solutions and have more trust in the government in serving the public interest.